Integrating rehabilitation services into primary health care: policy options for Iran - Saeed Shahabi; Carlotte Kiekens; Manal Etemadi; Parviz Mojgani; Ahmad Ahmadi Teymourlouei; Kamran Bagheri Lankarani (BMC Health Services Research, 2022)
Abstract Background Providing rehabilitation services in primary health care (PHC) is associated with numerous health, social, and economic benefits. Therefore, low and middle-income countries, such as Iran, should benefit from the advantages of integrating rehabilitation services into PHC. We conducted a qualitative study to determine policy solutions that could facilitate the integration of rehabilitation services into Iran’s PHC network. Methods Semi-structured interviews were conducted with 38 participants, including health policymakers, rehabilitation managers, faculty members, and rehabilitation practitioners. Purposive and snowball sampling strategies were adopted to recruit participants. The WHO Health System building blocks framework analysis was applied to analyze the collected data. Results Participants’ perspectives and experiences outlined potential policy options including: (1) stewardship: increasing political support, strengthening the leadership of the rehabilitation sector, and promoting inter-sectoral collaborations; (2) service delivery: increasing the knowledge of healthcare professionals, using local volunteers, deploying mobile rehabilitation teams, using telerehabilitation, and improving referral pathways; (3) financing: increasing government funding, preparing a package of rehabilitation services, and using appropriate payment mechanisms; (4) human resources: expanding rehabilitation workforce, training rehabilitation assistants, and enhancing employment and social opportunities; (5) information systems: establishing a comprehensive information system and an effective surveillance system; and (6) technologies: facilitating access to a range of rehabilitation equipment and raw materials, especially for prosthetics and orthotics services. Conclusion Based on the WHO six building blocks framework, this study identified several policy options for integrating rehabilitation services into the Iranian PHC Network. Some of the policy options include increasing political support, promoting inter-sectoral collaborations, increasing the skills and knowledge of healthcare workers, establishing effective referral pathways, strengthening team-working, and increasing government funding.